Collective ownership and land restitution: a new opportunity for Afro-Colombian communities - Peña Huertas, Rocío del Pilar (International journal of transitional justice, 2021)
Some contemporary liberal states incorporate provisions that protect the relationship between ethnic communities and their lands. However, such measures are quite fragile in terms of effectively protecting the communities against market dynamics. We argue that transitional justice systems, such as that currently being implemented in Colombia, provide the mechanisms to not only guarantee the restitution of the dispossessed lands that ethnic communities have lost during armed conflict, but also to strengthen property rights by providing some guarantees to transform the socioeconomic conditions of these communities and, ultimately, to act as a shield against market dynamics.